Research Progress on Printed Circuit Heat Exchangers (PCHEs) - Weng, Yanyan; Tian, Ke; Yang , Zhichen; Yang, Zengcheng (Scientific Journal of Technology, 2025)
The Printed Circuit Heat Exchanger (PCHE), an emerging microchannel compact heat exchanger, demonstrates significant application potential in cutting-edge fields such as supercritical carbon dioxide (S-CO₂) Brayton cycles, liquefied natural gas (LNG) processing, nuclear energy, and aerospace, owing to its exceptional compactness, high efficiency, and capability to withstand high pressures and temperatures. This review aims to systematically outline the research context, core findings, and existing controversies in PCHE technology, while also prospecting future research directions. Firstly, this paper introduces the fundamental structure, manufacturing process, and working principle of PCHEs. Subsequently, it provides a detailed review of major experimental and numerical simulation findings concerning their thermal-hydraulic characteristics under single-phase, two-phase, and supercritical conditions, with a focus on analyzing the performance optimization effects of channel geometries. Furthermore, it discusses key contentious points in current research, including the universality of correlations, the applicability of turbulence models, and performance uncertainties induced by manufacturing tolerances. Finally, based on current technological bottlenecks, future research is suggested to focus on intelligent multi-objective optimization design, the development of new materials and manufacturing processes, long-term reliability validation under extreme conditions, and artificial intelligence-based performance prediction and control.